Experience of using an electronic educational and methodological complex for organizing the independent work of students of the specialization cycle in orthodontics - Drohomyretska Мирослава Степанівна; Tkachenko Юлія В’ячеславівна; Polyanyk Наталія Ярославівна; Ostryanko Володимир Іванович; Arshynnikov Роман Сергійович; Sukhomlynova Тетяна Ярославівна (Actual Dentistry, 2023)
Summary. In this article we’ve had represented our experience of improvement in efficiency of educative process of «orthodontics» section by means of enhance-ment of the passive teaching methods and by means of development of the active ones. The passive teaching methods include improved teaching process of lecture material which has been formed into groups of problematique questions, and «lecturer-student» discussions. Active ones include the database of clinical situational tests for curricular and for extracurricular lessons training complex, consist of electronic aids and graphically visualized two types of tests have been made. Key words: orthodontics, students, active skills, self-study education, digital book, graphically visualized tests.